Handbook of analytical instruments - Khandpur, R. S. (McGraw-Hill McGraw-Hill Professional, 2006)
Analytical Instrumentation offers powerful qualitative and quantitative techniques for analysis in chemical, pharmaceutical, clinical, food-processing laboratories and oil refineries. It also plays a critical role in the monitoring and control of environment pollution. Over the years, this field has become extremely sophisticated. Today, microcontrollers and personal computers have been integrated into analytical instruments. This has brought in automation, efficiency and precision in analytical instrumentation. To keep users abreast of such advances, this edition of the Handbook of Analytical Instruments describes the principles and building blocks of analytical instrumentation. Recent advances in bio-sensors, gamma spectrometry, electron spin resonance (ESR) spectrometry, visualization methods for electrophoresis and several other tools and techniques of analytical instrumentation have been covered. In order to ensure that readers make the right decision, in terms of the instrument that best meets their requirements, the book includes a discussion of analytical instruments from various manufacturers. Useful for!.. ' Supervisors and technicians in clinical, pharmaceutical, food-processing laboratories and oil refineries. ' Personnel concerned with the monitoring and control of environmental pollution ' Service and maintenance engineers ' Post-graduate students of physics and chemistry undergoing courses in instrument analysis ' Students of instrumentation, electronics and chemical engineering.
Keywords: Chemistry; Analytical instrument